Heteronormativity in the Turkish education system: the experiences and survival strategies of LGBTQ plus teachers - Dogan, Muhammet Fatih (ELSEVIER SCI LTD, 2025)
This study analyzes the ways in which LGBTQ+ teachers in T & uuml;rkiye encounter the deeply embedded heteronormative structures of the education system and the coping strategies they develop in response. Against a backdrop of systemic issues such as the absence of explicit legal protection against discrimination based on sexual orientation and gender identity, judicial decisions that reinforce societal prejudices, and a curriculum that reproduces heterosexual norms this research centers on the lived experiences of these teachers. This study was conducted using a phenomenological design to understand the professional experiences of LGBTQ+ individuals as a specific phenomenon. The study group consisted of 20 teachers working in T & uuml;rkiye who identified as LGBTQ+. Data for the study was collected through semi-structured interviews. This approach is based on the premise that the collection of data about the individuals in the study group should not be limited to pre-prepared questions, but rather that individuals should be able to express themselves better through their own guidance. The findings, based on participant narratives, reveal that teachers experience a constant tension of disclosure, are pushed into silence through exclusion by their colleagues, and have their authentic identities suppressed under the guise of professionalism. While the study highlights an intergenerational difference, noting that students tend to be more accepting than colleagues, it also demonstrates that teachers lack institutional support in combating discrimination. The most striking conclusion is the adoption of identity concealment as a rational and long-term survival strategy, grounded in concrete fears such as job loss and social exclusion. Ultimately, the research underscores that heteronormativity transforms the school into a survival space for LGBTQ+ teachers, a situation that hinders both the well-being of the teachers and the creation of an inclusive educational climate for all students.
Keywords: LGBTQ plus teachers; Heteronormativity; Identity concealment; Workplace discrimination; Educational climate; Education & Educational Research